2012
DOI: 10.1155/2012/621968
|View full text |Cite
|
Sign up to set email alerts
|

Germ Cell Proteins in Melanoma: Prognosis, Diagnosis, Treatment, and Theories on Expression

Abstract: Germ cell protein expression in melanoma has been shown to correlate with malignancy, severity of disease and to serve as an immunologic target for therapy. However, very little is known about the role that germ cell proteins play in cancer development. Unique germ cell pathways include those involved in immortalization, genetic evolution, and energy metabolism. There is an ever increasing recognition that within tumors there is a subpopulation of cells with stem-cell-like characteristics that play a role in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 55 publications
1
13
0
1
Order By: Relevance
“…REC8 expression has been noted in melanoma [2] and we found it to be overexpressed in melanoma using western blot analysis (Figure 1) and immunofluorescence (Figure 2). REC8 has also been noted in irradiated lymphoma cells [22].…”
Section: Cohesion: How Not To Let Go Of Your Sistermentioning
confidence: 59%
See 3 more Smart Citations
“…REC8 expression has been noted in melanoma [2] and we found it to be overexpressed in melanoma using western blot analysis (Figure 1) and immunofluorescence (Figure 2). REC8 has also been noted in irradiated lymphoma cells [22].…”
Section: Cohesion: How Not To Let Go Of Your Sistermentioning
confidence: 59%
“…In fact, CIN is one of the most useful molecular markers to differentiate melanomas from benign nevi [1, 2]. Bastian et al found that 96.2% of melanomas demonstrated chromosomal aberrations while only 13.0% of benign nevi showed these same abnormalities, of which all were Spitz nevi with stable 11p duplications [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work from a range of organisms has revealed that tumors may acquire a more germline-like state. [4][5][6][7][8][9] Moreover, it has been demonstrated that the germline gene expression has the potential to be oncogenic in Drosophila melanogaster 4 and is associated with clinically more aggressive tumors in humans. 8 Janic et al recently demonstrated that l(3)mbt tumors in D. melanogaster ectopically expressed a broad range of germline genes, with up to a quarter of ectopically expressed genes being associated with a known germline function.…”
mentioning
confidence: 99%